ANALYZING THE CHALLENGES FACING THE ESG PRACTICES BY OIL AND GAS COMPANIES IN THE UAE (SBS Journal of Applied Business Research, 2026)
This study explores the key challenges that oil and gas companies in the United Arab Emirates (UAE) face in implementing effective Environmental, Social, and Governance (ESG) practices. As global pressure mounts for more sustainable and responsible business operations, the oil and gas sector—traditionally seen as a major contributor to environmental degradation—has come under intense scrutiny. The UAE, as a leading energy producer with a growing commitment to sustainability, represents a unique case where national vision and industry realities intersect.Environmental, Social, and Governance (ESG) practices are increasingly crucial within the oil and gas industry, driven by stakeholder demands, regulatory pressures, and the sector’s environmental footprint. The focus on ESG in oil and gas arises from the need to balance operational efficiency with the responsible management of resources, reduction of greenhouse gas (GHG) emissions, and the transition toward renewable energy sources. Companies in the sector are employing strategies to improve sustainability, such as carbon capture technologies, reducing methane emissions, and investing in low-carbon alternatives.Socially, there is a growing emphasis on workforce safety, community relations, and ethical supply chain management, with companies addressing these through enhanced safety protocols, stakeholder engagement, and transparency initiatives. Governance plays a critical role in enforcing these commitments, with firms prioritizing regulatory compliance, internal audits, and board diversity to strengthen accountability.The findings underscore the need for stronger regulatory frameworks, increased ESG literacy, and more transparent reporting mechanisms to bridge the gap between ambition and execution. Ultimately, this paper contributes to a deeper understanding of how ESG integration can be effectively advanced in the UAE’s oil and gas sector, aligning economic goals with long-term sustainability.